The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1136/archdischild-2012-302268
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and neonatal predictors of developmental coordination disorder in very low birthweight children

Abstract: Objective To identify perinatal and neonatal risk factors associated with developmental coordination disorder (DCD) in very low birthweight children (VLBW: <1250 g). Design Retrospective design with prospectively collected cohort. Setting Neonatal Follow-Up Program, Vancouver, Canada. Patients 157 VLBW children assessed at 4-5 years who were free of cerebral palsy or major neurological impairment and had full-scale IQ >70. Main outcome measure Movement Assessment Battery for Children (MABC).Results Using ≤15th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
1
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 27 publications
12
71
1
9
Order By: Relevance
“…Different care practices may have different effects especially on the vulnerability of the basal ganglia and cerebellum, which modify the profile/quality of movement in motor performance. Another difference compared to previous literature was that no effect of gender or small for gestational age status on the motor performance was found (4,9,10). This is consistent with our previous results of similar outcomes in small for gestational age infants (20)(21)(22).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Different care practices may have different effects especially on the vulnerability of the basal ganglia and cerebellum, which modify the profile/quality of movement in motor performance. Another difference compared to previous literature was that no effect of gender or small for gestational age status on the motor performance was found (4,9,10). This is consistent with our previous results of similar outcomes in small for gestational age infants (20)(21)(22).…”
Section: Discussionsupporting
confidence: 87%
“…A previous study of perinatal and neonatal predictors for DCD in very low birthweight children has shown that male sex, lower gestational age, lower birthweight, postnatal steroid exposure, longer duration of ventilation, more days of oxygen, retinopathy of prematurity, and hyponatremia were associated with poorer motor outcome. Of these variables, only male sex, low birthweight and postnatal steroid exposure remained significant with the addition of neonatal factors (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Boys are 1.7 to 2.8 times more likely than girls to have the disorder. 7,8 • Developmental coordination disorder is a prevalent childhood disability affecting 5%-6% of school-aged children.…”
Section: What Are the Risk Factors?mentioning
confidence: 99%
“…7 A retrospective study involving children 4-5 years of age confirmed the associations with male sex and low birth weight; it also found an association with postnatal exposure to steroids. 8 Children with developmental coordination disorder are at increased risk of being overweight or obese. 9 In a prospective, population-based cohort study in southwestern England, probable developmental coordination disorder was identified in 346 children aged 7-9.…”
Section: Box 1: Evidence Used In This Reviewmentioning
confidence: 99%